APPLICATION OF KOKANG LEAVES (Lepisanthes amoena (Hassk) Leenh.) AS AN ANTIOXIDANT IN COOKING OIL - Nurlaili, Nurlaili; Kamila, Adinda Putri; Valentina, Silva; Rahayu, Rosika; Pramalisa, Maria Cindy Amelia (PROSIDING SEMINAR KIMIA, 2023)
Cooking oil is widely used by the public as a medium for frying food ingredients. Heating during frying causes a decrease in the quality of the oil due to an oxidation reaction. Oxidized fatty acids and the resulting peroxide compounds harm the health of the body. The rate of oil oxidation can be inhibited by adding antioxidants to the oil. The cock plant (L. amoena (Hassk) Leenh.) is a wild plant from West Kutai, East Kalimantan, which has a high antioxidant content. The use of kokang leaves as an antioxidant is expected to inhibit oxidation in cooking oil. This study aims to determine the antioxidant activity of kokang leaves in cooking oil when heated. Peroxide number is used as an indicator of the level of oxidation that occurs in the oil. Peroxide number was measured by iodometric titration using thiosulfate solution as titration. Peroxide number analysis was carried out on three samples, namely cooking oil before heating, cooking oil after heating, and cooking oil after heating which had been mixed with dry cockle leaves. Heating is done for 1 minute. The results showed that the peroxide value of cooking oil mixed with kokang leaves was lower than the peroxide value without being mixed with kokang leaves. This study indicates that kokang leaves can be used as an antioxidant to inhibit the oxidation process in cooking oil. Keywords: antioxidant, kokang leaf, Lepisanthes amoena (Hassk) Leenh.), iodometric titration